Religious Tourism and its Role In increasing Tax Revenues: An Applied research in the General Commission of Taxes (Journal of Accounting and Financial Studies ( JAFS ), 2023)
The research aims to identify the concept of religious tourism in Iraq and shed light on the mechanism of applying the overnight tax in tourist hotels and its impact on tax revenues, as the tourism sector is one of the most developed industries in the countries of the world, and it is considered a productive sector and of great importance in its contribution to the gross domestic product. Gross and increase national income, and is a source of foreign currency, and tourist countries have deliberately exploited tourism in order to achieve more imports and supplement their reservoirs by imposing various tourism fees and taxes on tourists and visitors, and Iraq is one of the countries that possesses all the elements of religious tourism, in addition to possessing the oldest civilizations that go back By resting it for thousands of years with the presence of the shrines of the prophets, the saints and the righteous, which makes Iraq one of the most important centers of religious tourism attractions, and the research problem is about the failure of the General Authority for Taxes and its branches to impose the tourism tax because Iraq enjoys many and many elements of tourism of various kinds, including archaeological sites Historical, natural and religious, and that tourism activity and what it results in enhances tax revenues. As for the research methodology, the analytical descriptive approach was used, depending on the data and information of the Ministry of Planning - the Central Statistical Organization, the General Authority for Taxes, the Public Tourism Authority, the Holy Shrines, and related laws and instructions, and the research reached To the need to impose a hotel overnight tax on tourists because of its importance in increasing tax revenues and expanding and improving tourist facilities, thresholds and religious shrines in a way that accommodates large numbers of visitors.